Influence of Excitation on Photoluminescence Properties of Ag doped In2O3 thin Films Prepared by a Cost-effective Mechanism. (2015) - Sivaranjani, V.; Philominathan, P.; Kanmani, C.
Abstract: In this work, we present the results of photoluminescence (PL) by the Ag doped In 2 O 3 thin films prepared by a cost-effective and much simplified perfume atomizer technique. The PL emission behavior was investigated using three distinct excitation wavelengths (350 nm, 450 nm and 550 nm) upon the deposited films coated in a temperature range of 300° C to 450° C. The stokes shift towards red color for three different excitations was analysed and it has been shown that how the PL emission plays a crucial role in indentifying a good display device material. A highly intensed red emission was found commonly in all films with the excitation wavelength of 350 nm. All films exhibit four distinct emission peaks for the excitation wavelength of 450 nm and two low intensed emissions were found for the excitation wavelength of 550 nm. Further, the X-ray diffraction studies revealed the cubic In 2 O 3 structure with preferential orientation growth along (2 2 2) direction, irrespective of the variation in substrate temperature. A negative sign of Hall coefficient was confirmed the n-type conductivity of prepared samples and the optical parameters were also estimated from transmission data measured by UV-Vis-NIR spectrometer.